DERIVATIONAL POTENTIAL OF THE CONCEPT NAME “MOTHER” IN THE KOREAN AND UZBEK LINGUISTIC WORLDVIEWS - Vakhabova Malika Tolibjanovna (International Journal of Literature and Language Studies, 2026)
This article examines the derivational potential of the concept name mother in the Korean and Uzbek languages. The aim of the study is to identify universal and culture-specific patterns in the derivational potential of the concept name mother and to determine the cultural models underlying its linguistic representation. The research material consists of derivative formations based on the Korean lexemes 어머니 and 모(母), as well as the Uzbek lexeme ona. The study employs derivational, componential, comparative, and linguocultural methods of analysis. The findings demonstrate that the derivational field of the concept mother in Korean exhibits a dual-core structure based on the interaction between the native Korean lexeme 어머니 and the Sino-Korean root 모(母), whereas in Uzbek a single-core derivational nest is formed around the lexeme ona. The analysis reveals that Korean derivational patterns predominantly reflect kinship, origin, and family hierarchy, while Uzbek derivational models emphasize emotional-evaluative and moral-axiological meanings. Based on the obtained results, two types of derivational conceptualization of motherhood are identified: the structural-hierarchical type and the axiological-emotional type.